Thermoregulation in winter swimmers and physiological significance of human catecholamine thermogenesis - Vybíral, S; Lesná, I; Jansky, L; Zeman, V (Experimental physiology, 2000)
Thermoregulation in control subjects and cold-adapted winter swimmers was examined during 1 h of cold water immersion (13 C). It was found that the thermoregulatory functions of winter swimmers differ from those of non-cold-adapted subjects. As evident from the relationship between rectal temperature and the magnitude of cold thermogenesis, in controls a significant part of cold thermogenesis during the early phase of cooling was induced by changes in peripheral temperature input, while in the late phase of cooling it was the central temperature input which was mainly engaged in induction of cold thermogenesis. In winter swimmers the magnitude of cold thermogenesis was solely related to changes in rectal temperature, indicating the predominance of the central temperature input in activation of heat production mechanisms. The thermoregulatory threshold for induction of cold thermogenesis was lowered (by 0.34 C), but the apparent hypothalamic thermosensitivity was the same as in non-cold-adapted subjects. These differences are indicative of adaptation of thermoregulatory control centres. Additionally, the activity of thermoregulatory effectors was also changed. Shivering was induced later during cooling (after 40 min) in winter swimmers than in controls, which suggests an important participation of non-shivering thermogenesis in the early thermogenic response. Winter swimmers also showed bradycardia and a greater reduction in plasma volume during cooling. The data indirectly indicate restriction of heat loss from the body. Only a non-significant increase in quantity of subcutaneous fat was observed in winter swimmers. Thus, winter swimmers were able to survive a significantly greater temperature gradient between body and environment than non-cold-adapted subjects by modifying the sensory functions of hypothalamic thermoregulatory centres to lower heat loss and produce less heat during cold exposure. Additionally, the capacity of the total cold thermogenesis due to potentiation of non-shivering heat production was also increased. Heat produced due to thermogenic action of adrenaline may represent more than a quarter of the total cold thermogenesis. In conclusion, the data suggest that winter swimmers exhibit metabolic, hypothermic and insulative types of cold adaptation.
Keywords: krevní tlak; fyziologická adaptace; Body Temperature; Cold Temperature; Body Temperature Regulation; mužské pohlaví; plavání; nízká teplota; Adult; Heart Rate; tělesná teplota; noradrenalin; srdeční frekvence; ženské pohlaví; Plasma Volume; adrenalin; Blood Pressure; Humans; Hemodynamics; Catecholamines; Swimming; hemodynamika; termoregulace; dospělí; Norepinephrine; Female; katecholaminy; Epinephrine; lidé; Male; Adaptation, Physiological; objem plazmy